EXPLORING THE MEDIATION EFFECT OF PERCEIVED USEFULNESS ON CROP DIVERSIFICATION DRIVERS AMONG SMALLHOLDER COCOA FARMERS IN TANZANIA - Molela, Godfrey (Applied Studies in Agribusiness and Commerce, 2025)
The living standard of smallholder cocoa farmers in Tanzania was still low despite the recent transformation in marketing structure which led to the sharp rise in price. This study aimed at examining the drivers for smallholder cocoa farmers in Kilombero, Tanzania to engage in multiple crops farming as the means of poverty alleviation. Based on the cross-sectional survey design, primary data were collected from 501 cocoa farmers obtained through a random selection process that was conducted in their respective 162 agricultural marketing and cooperative societies (AMCOS) found in Kilombero. Results from covariance-based structural equation modeling (SEM) revealed that, cocoa market price, payment waiting time, farm size and cocoa farm income played significant roles in cocoa farmers’ decisions to invest while taking into account their perceptions of success. It was only the off-farm income factor that was found to have no statistical significance on farmers’ decision to invest while considering the mediation effect of perception. The study just assessed the investment decisions by smallholder cocoa farmers in Tanzania. Policy makers need to enhance the marketing factors such as cocoa price and payment time to boost farmers’ financial muscles. Meanwhile, farmers themselves are advised to take measures to boost production by increasing farm sizes while adopting better agronomic as per extension officers’ training.This study contributed to knowledge gap by exploring the cocoa-related factors that affect the stallholders’ decision to invest in crop diversification other than the non-cocoa factors that were investigated in previous studies.